The Effects of Methylprednisolone and Hyaluronic Acid on the Endometrium in Experimentally Induced Asherman Syndrome Rat Models: A Prospective Laboratory Study - Mehmet Genco; Merve Genco; Fisun Vural; Nermin Koç (Medicina)
Background and Objectives: The current study was designed as a prospective laboratory investigation to evaluate the histopathological effects and VEGF (vascular endothelial growth factor) expression in uterine tissue following treatment with a combination of methylprednisolone and hyaluronic acid in a rat model of experimentally induced Asherman Syndrome. Materials and Methods: Twenty-six female Sprague-Dawley rats were used. Trichloroacetic acid was applied to the right uterine horns of all the groups to induce adhesion formation. First, we induced the Asherman model in two rats (Group 1). The remaining rats were divided into the following three groups: Group 2 received intrauterine hyaluronic acid treatment, Group 3 received oral methylprednisolone treatment, and Group 4 received both treatments. Inflammation, gland count, and fibrosis levels were assessed histopathologically. VEGF levels were analyzed immunohistochemically. Results: Hyaluronic acid treatment increased the uterine lumen diameter and vascularization. Methylprednisolone treatment increased the gland count and uterine wall thickness while decreasing the inflammation and fibrosis scores. Combined treatment provided a statistically significant advantage over single treatments. In particular, the combined treatment group exhibited significantly lower fibrosis (p = 0.184) and inflammation scores (p = 0.071), as well as higher gland counts (p = 0.849) and VEGF expression (p = 0.114), compared to the groups receiving only methylprednisolone or hyaluronic acid. These differences indicate that the synergistic effect of the two agents results in more effective endometrial healing than when either treatment is applied alone. Conclusions: Methylprednisolone treatment significantly prevented adhesion formation and reduced the inflammation and fibrosis scores compared to hyaluronic acid treatment alone. The combined treatment adds to the effects of the hyaluronic acid treatment alone and provides better healing.